Comparison of Endemic and Epidemic Vesicular Stomatitis Virus Lineages in Culicoides sonorensis Midges - Paula Rozo-Lopez; Steven J. Pauszek; Lauro Velazquez-Salinas; Luis L. Rodriguez; Yoonseong Park; Barbara S. Drolet (Viruses, 2022)
Vesicular stomatitis virus (VSV) primarily infects livestock and is transmitted by direct contact and vectored by Culicoides midges (Diptera: Ceratopogonidae). Endemic to Central and South America, specific VSV lineages spread northward out of endemic regions of Mexico and into the U.S. sporadically every five to ten years. In 2012, a monophyletic epidemic lineage 1.1 successfully spread northward into the U.S. In contrast, the closest endemic ancestor, lineage 1.2, remained circulating exclusively in endemic regions in Mexico. It is not clear what roles virus-animal interactions and/or virus-vector interactions play in the ability of specific viral lineages to escape endemic regions in Mexico and successfully cause outbreaks in the U.S., nor the genetic basis for such incursions. Whole-genome sequencing of epidemic VSV 1.1 and endemic VSV 1.2 revealed significant differences in just seven amino acids. Previous studies in swine showed that VSV 1.1 was more virulent than VSV 1.2. Here, we compared the efficiency of these two viral lineages to infect the vector Culicoides sonorensis (Wirth and Jones) and disseminate to salivary glands for subsequent transmission. Our results showed that midges orally infected with the epidemic VSV 1.1 lineage had significantly higher infection dissemination rates compared to those infected with the endemic VSV 1.2 lineage. Thus, in addition to affecting virus-animal interactions, as seen with higher virulence in pigs, small genetic changes may also affect virus-vector interactions, contributing to the ability of specific viral lineages to escape endemic regions via vector-borne transmission.